Análise da genotoxicidade das águas da Lagoa da Extremoz - RN - Barbosa, Jefferson da Silva (2008)
The contamination of the waters resources for wastewater from industrial, agricultural, and domestic sources is a serious environment problem, compromising its use for human consumption and agriculture. The Extremoz-RN Lake is an important freshwater source for the supply of the city of Natal, supplying a population of approximately 160,000 habitants. This aquatic body is located near an industrial pole which can be a serious risk factor for quality of its waters. The objectives of this study were examined the genotoxicity of Extremoz Lake between September of 2006 and January of 2008, by a combination of the Allium micronucleus test, piscine micronucleus test and the comet assay in erythrocytes from peripheral blood of Oreochromis niloticus. Additionally, the level of eight different heavy metals was quantified through spectrometry of atomic absorption of flame. The Allium test did not detect increase in the frequencies of micronucleus in none of the analyzed periods, however a strong cytotoxic activity was demonstrated for decrease in mitotic index in the analyses carried in April and July of 2007. Negative results had been detected in the frequencies of micronucleus in O. niloticus. A statistic significant increase was observed in the levels of DNA damage in comet assay carried in July of 2007. The results of the chemical analysis had detected increase in the levels of cadmium, chromium, copper, nickel, lead and zinc in different periods. These results demonstrated an alteration of the water s quality of the Extremoz Lake caused for the contamination for heavy metals and increase of DNA strand breaks. The use of biomonitoring program of the heavy metal and other pollutants with genotoxic potential combinated with genotoxicity assays is recommends.